Prognostic value of CD103+ tumor-infiltrating lymphocytes and programmed death ligand-1 (PD-L1) combined positive score in recurrent laryngeal squamous cell carcinoma. (December 2022) - Smith, Joshua D.; Bellile, Emily L.; Ellsperman, Susan E.; Heft-Neal, Molly E.; Mann, Jacqueline E.; Birkeland, Andrew C.; Hoesli, Rebecca C.; Swiecicki, Paul L.; Worden, Francis P.; Schonewolf, Caitlin; Shah, Jennifer L.; Mierzwa, Michelle L.; et al.
Highlights: Recurrent larynx cancers vary in tumor-infiltrating lymphocytes and PD-L1 staining. CD103 + lymphocyte infiltration only modestly correlates with PD-L1 staining. CD4 + and CD8 + lymphocyte infiltration does not correlate with PD-L1 staining. CD103 + lymphocytes and PD-L1 staining predict survival in recurrent larynx cancer. Abstract: Objectives: In an evolving era of immunotherapeutic options for persistent or recurrent laryngeal squamous cell carcinoma (LSCC), there is a need for improved biomarkers of treatment response and survival to inform optimal treatment selection and prognostication. Herein, our primary objective was to explore correlations between tumor infiltrating lymphocytes (TILs) and PD-L1 Combined Positive Score (CPS). Secondarily, we sought to explore their combined association with survival outcomes in patients with persistent or recurrent LSCC treated with salvage surgery. Materials and Methods: This was a retrospective cohort study at a single academic medical center. Immunohistochemistry staining for TILs and PD-L1 was performed on a tissue microarray of persistent or recurrent LSCC pathologic specimens. Correlations between TIL subsets and PD-L1 CPS were examined using Pearson's correlation coefficient and survival outcomes were analyzed with the Kaplan-Meier method and log-rank tests. Results: Only CD103 + TILs showed a statistically significant, weakly-positive correlation with PD-L1 CPS (r 2  = 0.264, p  < 0.015). No other TIL subsets correlated with PD-L1 CPS in our cohort. The most favorable survival outcomes were seen in patients with pathologic N0 tumors showing high CD103 + TILs and/or high PD-L1 CPS staining. Conclusion: Among patients with persistent or recurrent LSCC, CD103 + TILs only modestly correlated with PD-L1 CPS. A combined biomarker score incorporating CD103 + TILs and PD-L1 CPS greatly enhanced survival discrimination. This model may have additional utility in predicting the clinical benefit of immunotherapies in persistent or recurrent LSCC in the future.